"You're Just a Mental Health Nurse": Nurses' Experiences of Associative Stigma When Accessing Physical Health Care for Their Patients. (1st February 2023) - Domingue, Jean-Laurent; Jager, Fiona; Lusk, Jodi; Pryer, Billie; Ezeani, Celestina; Davis, Alexandra
Abstract: In this article, we present the results of an interpretive phenomenology looking at mental health nurses' experiences of associative stigma when accessing physical health care for their patients. Our results illustrate the multifaceted dynamics of stigma in the context of mental health nursing and the direct impacts stigmatizing behaviors have on mental health nurses and patients alike, including an impeded access to health care services, loss of social status and personhood, and the internalization of stigma. They also highlight how nurses resist to stigma and how they help their patients cope with stigmatization.